High-frequency diffraction contribution by planar metallic–DNG metamaterial junctions. Issue 10 (1st December 2020) - Gennarelli, G.; Riccio, G.
Abstract: The plane wave diffraction by a planar junction consisting of a thick metallic sheet and a lossy double-negative metamaterial slab is studied by using the Uniform Asymptotic Physical Optics approach. This approach assumes the radiation integral as a starting point and uses the physical optics surface currents as sources to be integrated. The integral is manipulated by taking advantage of useful approximations and evaluations, and re-formulated in order to apply an asymptotic procedure able to generate a closed-form approximate solution in the framework of the Uniform Geometrical Theory of Diffraction. Accordingly, advantages and drawbacks result from the application of the proposed solution. The jumps of the geometrical optics field are compensated. Implementation and handling of the computer code are facilitated by the evaluation of well-known functions and parameters. No differential/integral equations or special functions must be computed.